ATTRACTIVENESS OF THE EASTERN AUKŠTAITIJA REGION FOR LOCAL TOURISM UNDER COVID-19 CONDITIONS - Narkūnienė, Ramutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article discusses the attractiveness factors of the Eastern Aukštaitija region for local tourism under COVID - 19 conditions and presents the results of the research (analysis of scientific literature, questionnaire surveys and analysis of strategic documents). The aim of the research is to perform an analysis of the attractiveness of the Eastern Aukštaitija region for local tourism under COVID-19 conditions. Objectives of the research: to describe the factors of tourism region's attractiveness for local tourism; to perform an analysis of the attractiveness of the Eastern Aukštaitija region for local tourism under COVID-19 conditions. An analysis of the scientific literature showed that destination attractions define the framework within which visitors enjoy their vacations. They include all forms of natural and created (manmade) resources, culture, heritage, history, customs, architectural features, traditional artwork, cuisine, music and handicrafts that attract travellers. According to the results of the research, the choice of travels in the Eastern Aukštaitija region is mostly influenced by such factors of attractiveness of the region as natural resources, cultural resources and interesting places of interest, as well as attractiveness of the tourism destination/ region.